Metabolic Syndrome Is Associated With Impaired Insulin-Stimulated Myocardial Glucose Metabolic Rate in Individuals With Type 2 Diabetes: A Cardiac Dynamic 18F-FDG-PET Study - Succurro, Elena; Vizza, Patrizia; Papa, Annalisa; Cicone, Francesco; Monea, Giuseppe; Tradigo, Giuseppe; Fiorentino, Teresa Vanessa; Perticone, Maria; Guzzi, Pietro Hiram; Sciacqua, Angela; Andreozzi, Francesco; Veltri, Pierangelo; et al. (Frontiers in Cardiovascular Medicine, 2022)
Metabolic syndrome is a condition characterized by a clustering of metabolic abnormalities associated with an increased risk of type 2 diabetes and cardiovascular disease. An impaired insulin-stimulated myocardial glucose metabolism has been shown to be a risk factor for the development of cardiovascular disease in patients with type 2 diabetes. Whether cardiac insulin resistance occurs in subjects with metabolic syndrome remains uncertain. To investigate this issue, we evaluated myocardial glucose metabolic rate using cardiac dynamic 18F-FDG-PET combined with euglycemic-hyperinsulinemic clamp in three groups: a group of normal glucose tolerant individuals without metabolic syndrome (n=10), a group of individuals with type 2 diabetes and metabolic syndrome (n=19), and a group of subjects with type 2 diabetes without metabolic syndrome (n=6). After adjusting for age and gender, individuals with type 2 diabetes and metabolic syndrome exhibited a significant reduction in insulin-stimulated myocardial glucose metabolic rate (10.5±9.04 mol/min/100g) as compared with both control subjects (32.9±9.7 mol/min/100g; P<0.0001) and subjects with type 2 diabetes without metabolic syndrome (25.15±4.92 mol/min/100g; P=0.01). Conversely, as compared with control subjects (13.01±8.53 mg/min x Kg FFM), both diabetic individuals with metabolic syndrome (3.06±1.7 mg/min x Kg FFM, P=0.008) and those without metabolic syndrome (2.91±1.54 mg/min x Kg FFM, P=0.01) exhibited a significant reduction in whole-body insulin-stimulated glucose disposal, while no difference was observed between the 2 groups of subjects with type 2 diabetes with or without metabolic syndrome. Univariate correlations showed that myocardial glucose metabolism was positively correlated with insulin-stimulated glucose disposal (r= 0.488, P=0.003), and negatively correlated with the presence of metabolic syndrome (r= -0.743, P<0.0001) and with its individual components. In conclusion, our data suggest that an impaired myocardial glucose metabolism may represent an early cardio-metabolic defect in individuals with the coexistence of type 2 diabetes and metabolic syndrome, regardless of whole-body insulin resistance.